2019
DOI: 10.1016/j.jceh.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Simplified Criteria for Autoimmune Hepatitis in Children: Systematic Review and Decision Analysis

Abstract: Background/objectives: Several studies have been conducted on the accuracy of simplified criteria for autoimmune hepatitis that were presented in 2008 as an alternative to original criteria. Our purpose is to summarize the evidence available regarding their accuracy in children and to carry out a basic clinical decision analysis based on it. Methods: Electronic and manual searches were performed with keywords related to diagnostic validity terms. Data from included studies were extracted, and summary estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
0
7
0
1
Order By: Relevance
“…In children, a meta-analysis of four studies pertaining to the accuracy of the simplified criteria revealed a sensitivity of 77% and a specificity of 95%. (123) In that study, false-negative scores (~17%) were associated with seronegative AIH.…”
Section: Diagnostic Scoring Systemsmentioning
confidence: 79%
“…In children, a meta-analysis of four studies pertaining to the accuracy of the simplified criteria revealed a sensitivity of 77% and a specificity of 95%. (123) In that study, false-negative scores (~17%) were associated with seronegative AIH.…”
Section: Diagnostic Scoring Systemsmentioning
confidence: 79%
“… 31 , 32 A recent systematic review suggested that the simplified scoring system also provided high specificity and moderate sensitivity for the diagnosis of pediatric AIH. 33 On the other hand, in a Korean cohort of patients with AIH (n=343; mean age, 52.8 years old), definite/probable AIH according to the revised and simplified criteria were found to be 24.8%/65.4% and 34.4%/38.5%, respectively, and the concordance rate was quite low (38.8%), with modest sensitivity of the simplified criteria. 10 …”
Section: Diagnosis: a Clinical Diagnosismentioning
confidence: 93%
“…Although retrospectively, the high specificity and specificity of the simplified scoring system in AIH diagnosis has been validated by various studies 9‐12 …”
Section: Introductionmentioning
confidence: 99%